Probiotic Fermentation of Defatted Cottonseed Meal for Sustainable Foods and Non-Food Applications - Yan, Zhanqiang; Li, Tian; Zou, Gen; Zhang, Xiaoling; Qu, Lingbo; Wei, Yongjun (Microorganisms (Basel), 2025)
Cottonseed is a valuable source of high-quality proteins and oils. Defatted cottonseed meal (DCSM), a by-product of cottonseed oil extraction, holds significant potential as a sustainable protein resource. This review outlines the chemical composition, structural features, and unique properties of cottonseed, with a focus on its inherent antinutritional factors, such as gossypol. Strategies for enhancing the utilization of DCSM as a protein source are systematically evaluated, including physical, chemical, and biological methods used to eliminate or reduce antinutritional components. Among these, microbial fermentation, particularly solid-state fermentation, is highlighted as a promising, eco-friendly approach for detoxification and nutritional improvement. This review further discusses critical factors influencing the removal of anti-nutritional compounds, such as pretreatment methods, fermentation parameters, and microbial strains. The efficacy of probiotic strains (e.g., Bacillus and yeasts) in enhancing the protein digestibility, amino acid profiles, and functional properties of DCSM is discussed. Additionally, recent advances in the application of fermented cottonseed protein in foods (e.g., animal feed, functional peptides, and food additives) and non-food sectors (e.g., biofuels and bioplastic) are explored. The integration of probiotic-driven fermentation processes is proposed as a strategy to exploit the full nutritional and economic potential of DCSM, paving the way for its broader and sustainable use in foods and non-food applications.